Integration design of 2.4 ghz microstrip patch with siw antenna structure - Panerselvan, Kamleshvari; Nurul Afifi, Alias; Mohamad Shaiful, Abdul Karim; Ahmad Syahiman, Mohd Shah; Syamimi Mardiah, Shaharum (Institution of Engineering and Technology, 2022)
In this paper, the integration design of the microstrip patch antenna with SIW antenna structure was proposed. SIW technology represents an emerging for the development of circuit and components operating in the microwave and millimeter-wave region. The proposed rectangular microstrip antenna by adding SIW technique is stimulated at 2.4 GHz operating frequency with Teflon dielectric constant 2.1 and loss tangent equal to 0.0002 to analyze the antenna performance. For the simulation, antennas are numerically investigated using High-Frequency Structure Simulator (HFSS) software. The simulation result shows that with the integration of the SIW design, the antenna gain can be significantly improved. Moreover, a very significant improvement of thereturn loss of -22.63 dB comparing to the original patch antenna which only reported to obtained return loss of -10.36dB.